Omicron spike function and neutralizing activity elicited by a comprehensive panel of vaccines - Bowen, John E; Addetia, Amin; Dang, Ha V; Stewart, Cameron; Brown, Jack T; Sharkey, William K; Sprouse, Kaitlin R; Walls, Alexandra C; Mazzitelli, Ignacio G; Logue, Jennifer K; Franko, Nicholas M; Czudnochowski, Nadine; et al. (Science (American Association for the Advancement of Science), 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant of concern comprises several sublineages, with BA.2 and BA.2.12.1 having replaced the previously dominant BA.1 and with BA.4 and BA.5 increasing in prevalence worldwide. We show that the large number of Omicron sublineage spike mutations leads to enhanced angiotensin-converting enzyme 2 (ACE2) binding, reduced fusogenicity, and severe dampening of plasma neutralizing activity elicited by infection or seven clinical vaccines relative to the ancestral virus. Administration of a homologous or heterologous booster based on the Wuhan-Hu-1 spike sequence markedly increased neutralizing antibody titers and breadth against BA.1, BA.2, BA.2.12.1, BA.4, and BA.5 across all vaccines evaluated. Our data suggest that although Omicron sublineages evade polyclonal neutralizing antibody responses elicited by primary vaccine series, vaccine boosters may provide sufficient protection against Omicron-induced severe disease.